Radiological comparison of conventional versus modified sauvé–kapandji procedure with stabilization of the proximal ulnar stump using the extensor carpi ulnaris tendon: A retrospective case–control study. Issue 11 (March 2018) - Tomori, Yuji; Sawaizumi, Takuya; Nanno, Mitsuhiko; Takai, Shinro
Abstract : Abstract: The Sauvé–Kapandji procedure is a reliable option for patients with various disorders of the distal radioulnar joint (DRUJ). However, postoperative pain over the proximal ulnar stump frequently develops during forearm rotation or when lifting heavy objects, although many clinically satisfactory results have been reported. This stump pain has been suggested to result from dynamic instability of the proximal ulnar stump. Several types of tenodesis have recently been performed simultaneously with the Sauvé–Kapandji procedure to stabilize the proximal ulnar stump and thus relieve the associated pain. Although satisfactory outcomes of these stabilization procedures have been reported, correlations of the residual symptoms and radiographic findings between the conventional method and the modified method. Additionally, the mechanism of pain relief remains unclear. To elucidate the cause of proximal ulnar stump pain, the clinical results and radiographic changes were compared between 2 treatment groups in which different Sauvé–Kapandji procedures had been performed. Twenty-four wrists with distal radioulnar disorders, all of which had undergone Sauvé–Kapandji procedures, were retrospectively classified into 2 groups according to the procedure. Group A (13 wrists) was treated by the conventional surgical procedure, in which the proximal ulnar stump is not stabilized. Group B (11 wrists) was treated by the modified method, in which the proximal ulnar stump is stabilized by tenodesis with the extensor carpi ulnaris tendon. Wrist pain, proximal ulnar stump pain, ranges of forearm pronation/supination, and grip strength were investigated. The ulnar distance, ulnar gap, interosseous distance, and dorsopalmar distance were measured on both resting and dynamic radiographs. Stump pain was recognized in 6 wrists in group A and 0 in group B. However, no substantial differences in the other clinical findings or 4 radiographic parameters were found between the 2 groups. These findings suggest that stabilization of the proximal ulnar stump cannot correct either dorsal ulnar deviation or dorsal displacement of the radius. Therefore, proximal ulnar stump pain may not be caused by either radial or dorsal deviation of the proximal ulnar stump but instead by other dynamic factors.